Philosophy of Austrian economics - Extended cut - Alexander Linsbichler (Duke University, Center for the History of Political Economy (CHOPE), 2021)
Carl Menger's Principles of Economics, published in 1871, is usually regarded as the founding document of the Austrian School of economics. Many of the School's prominent representatives, including Friedrich Wieser, Eugen Böhm-Bawerk, Ludwig Mises, Hans Mayer, Friedrich August Hayek, Fritz Machlup, Oskar Morgenstern, and Gottfried Haberler, as well as Israel Kirzner, Ludwig Lachmann, Murray Rothbard, Don Lavoie, and Peter Boettke, advanced and modified Menger's research program in sometimes conflicting ways. Yet, some characteristics of the Austrian School remain (nearly) consensual from its foundation through to contemporary neo-Austrian economists. In eight sections, we will briefly discuss some of the philosophical and methodological characteristics of Austrian economics: Austrian action theory and interpretative understanding, a relatively thoroughgoing subjectivism, methodological individualism, ontological individualism, apriorism, essentialism, an often overstated rejection of formal methods, and alertness to economic semantics.
Keywords: B13; B25; B40; B53; C18; 330; Austrian economics; methodology; subjectivism; individualism; apriorism; praxeology; essentialism; formal methods; economic semantics